(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2023)
Among natural sources we mainly consider the plant-based phytochemicals. Phytochemicals or the secondary metabolites are the extract obtained from the herbal plants which may serve as a great venture for their utilization as nanomedicine. Drugs or compounds converted to nano range shows unique characteristics which lengthen circulation, ameliorate localization, improve drug efficiency, etc. Nanomedicine is the type of formulation which uses the nanotechnology to deliver the drug in the form of nanoparticles incorporated within the nanocarriers. Nanocarriers intensify solubility and stability of phytochemicals, prolong their half-life in blood and achieve sitetargeting delivery. The development of phyto-based nano formulations has been explored to have potential applications in managing life-threatening diseases. The present review highlights the compilation on the potential of phyto nanotherapeutics over the conventional treatments against various serious leading disorders. Dhaka Univ. J. Pharm. Sci. 22(1): 115-124, 2023 (June)